Bacterial oxycarotenoids added into broiler chickens ration modify breast meat color - Ponsano, Elisa Helena Giglio [UNESP]; Avanço, Saulo Vinícius [UNESP]; Garcia Neto, Manoel [UNESP]; Minello, Maria Clara da Silva [UNESP]; Grassi, Thiago Luís Magnani [UNESP]; Santo, Edson Francisco do Espírito [UNESP]; Costa, Alstyn Wesley Momette da [UNESP]; Pinto, Marcos Franke [UNESP] (My University, 2012)
Some markets around the world demand for well pigmented poultry products, what justifies the intentional use of synthetic additives in rations during breeding. The inconvenient for that practice most times is the elevated price of these products, beyond the argument of being chemicals, which may not be viable for some production systems. So, the aim of this experiment was to check on the ability of natural red oxycarotenoids produced by R. gelatinosus to modify broilers breast meat color. Bacterial biomass containing oxycarotenoids were added into Cobb broilers finisher diets at 0, 1.0, 2.0 and 3.0 g/kg and fed during 10 days (35-45 d). Five replicates (10 birds each) were performed. At days 35, 37, 39, 41, 43 and 45, 100 birds were slaughtered scalded, defeathered and eviscerated. Data on live and carcass weights were recorded. After cooling, color parameters of meat were determined on breast surface using a HunterLab XE Plus colorimeter calibrated with black and white standard tiles. Regression analysis was used for the investigation of relationships between days of consumption and biomass concentration on color values, live weight and carcass yield. Results showed that redness of breast meat was significantly influenced by the biomass concentration in a linear effect (P=0.0056) and also by the time of consumption, in a quadratic effect (P=0.0232). Days of consumption also affected yellowness and lightness with significant quadratic responses (P=0.0225 and P<0.0001, respectively). Birds live weight increased significantly during the application of the experimental diets (P<0.0001), showing no negative influence of the biomass administration. Also no deleterious effects derived from the application of the product were observed on carcass yield. So we concluded that R. gelatinosus oxycarotenoids present in the bacterial biomass can modify broilers breast meat color, performing as an alternative pigmenting additive in poultry production.
Keywords: Rubrivivax gelatinosus; Biomass; Redness; Lightness; Carcass yield